2011
DOI: 10.1021/ed2001494
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Photoluminescent and Triboluminescent Copper(I) Compound: An Experiment for an Advanced Inorganic Chemistry Laboratory

Abstract: A simple synthesis is proposed from inexpensive reactants of a copper(I) derivative that exhibits strong photoluminescence and, in the crystalline form, exhibits strong triboluminescence. This laboratory provides an opportunity for introducing students to the phenomenon of triboluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
0
33
0
2
Order By: Relevance
“…[9][10][11] A limited number of triboluminescent transition metal (TM) complexes have also been reported, including Ru II , 12 Pt II , 13 Mn II , [14][15][16] and Cu I . [17][18][19][20][21][22] Considering that Cu is one of the most abundant and inexpensive metals, TL materials based on Cu present a practical alternative to currently utilized Eu-and Tb-based materials. Until now, only a few scattered examples of triboluminescent crystalline Cu complexes have been published, featuring very diverse ligand frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] A limited number of triboluminescent transition metal (TM) complexes have also been reported, including Ru II , 12 Pt II , 13 Mn II , [14][15][16] and Cu I . [17][18][19][20][21][22] Considering that Cu is one of the most abundant and inexpensive metals, TL materials based on Cu present a practical alternative to currently utilized Eu-and Tb-based materials. Until now, only a few scattered examples of triboluminescent crystalline Cu complexes have been published, featuring very diverse ligand frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only a few scattered examples of triboluminescent crystalline Cu complexes have been published, featuring very diverse ligand frameworks. [17][18][19][20][21][22][23] In all but one of these reports, however, no systematic experimental data were collected. 24 All of these reports are also examples of fractoluminescence, where a crystal is required to observe the TL effect.…”
Section: Introductionmentioning
confidence: 99%
“…MnBr 4 , which were ascribed to phosphorescence from the 4 T 1 / 6 A 1 transition of the central Mn ions 61. Pettinari et al and Marchetti et al found the TL of copper chelates 62,63.…”
mentioning
confidence: 98%
“…Marchetti et al beschrieben 2012 die äußerst beeindruckende blaugrüne Tribolumineszenz des Komplexes Kupfer(I)‐(bis‐pyridin‐triphenylphosphin)thiocyanat [29] und seine Synthese. Der Komplex ist sehr berührungsempfindlich.…”
Section: Das Experimentsunclassified
“…So bildet z. B. Kupfer(I)thiocyanat mit Triphenylphosphin (PPh 3 ) und Pyridin den gut kristallisierenden Komplex [Cu(SCN)(py) 2 (PPh 3 )] mit einer sehr intensiven, blaugrünen Tribolumineszenz [50]. Die Emission der Tribolumineszenz stimmt mit der Fluoreszenzemission überein.…”
Section: Das Experimentsunclassified